Strategi Komunikasi Pariwisata dalam Pengelolaan Ekowisata Bahari di Taman Nasional Bunaken - Laluas, Efraim; Wilantari, Ni Nyoman Ayu; Selti, Selti (Fakultas Dharma Duta, 2025)
Bunaken National Park is one of Indonesia's leading marine tourism destinations, which has high biodiversity but also faces pressure from tourism activities. This study aims to analyze tourism communication strategies in the management of marine ecotourism in Bunaken using a literature review method. The results of the study show that tourism communication plays a strategic role in supporting the sustainability of destinations through five main dimensions, namely: (1) promotional and marketing communication to build Bunaken's image as a sustainable destination, (2) interpretive communication in conveying ecological education to tourists, (3) cross-cultural communication to improve the intercultural competence of tourism stakeholders, (4) participatory communication that places local communities as the main actors in management, and (5) environmental communication and issue management to maintain the image of the destination from ecosystem damage and negative publicity. This study confirms that the success of Bunaken's management is not only determined by ecological conservation and infrastructure development, but also by the effectiveness of a holistic, integrative, and sustainable tourism communication strategy.